ANALISIS WACANA KORELASI DIKSI AHMAD HASSAN DAN AHMAD DAHLAN PERSPEKTIF DAKWAH DI INDONESIA - Setiawan; Abdul Munir Mulkhan; Zamah Sari (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study analyzes the use of diction in da'wah writings delivered by two great scholars in the history of Islam in Indonesia, namely Ahmad Hassan and Ahmad Dahlan. The writings studied are Ahmad Hassan's writing entitled “High Modesty in Islam” and Ahmad Dahlan's writing entitled “The Unity of Human Life”. This research is focused on diction which is specialized again on the study of standard and substandard language, scientific words and popular words. This research uses a descriptive qualitative method that examines based on the phenomena written in the works of the two figures and described as a description of the results of the analysis. The results of this study indicate that the diction used by the two figures reflects differences but is still correlated because Ahmad Hassan uses more standard and scientific language diction so that the spread of da'wah can only be done to educated people or certain groups who study the science. Meanwhile, Ahmad Dahlan prefers standard and popular language diction so that the da'wah given through his writings can be accepted by all levels of society from the top to the bottom. This is evidenced by Ahmad Hassan Dahlan's use of popular words 10 diction while Ahmad Dahlan up to 18 diction but Ahmad Hassan's use of scientific words reached 5 diction while Ahmad Dahlan did not use scientific words.Keywords: Diction, Ahmad Hassan, Ahmad Dahlan, Da’wah.